Common genetic variants improve risk stratification after the atrial switch operation for transposition of the great arteries. (15th January 2023) - Woudstra, Odilia I.; Skoric-Milosavljevic, Doris; Mulder, Barbara J.M.; Meijboom, Folkert J.; Post, Marco C.; Jongbloed, Monique R.M.; van Dijk, Arie P.J.; van Melle, Joost P.; Konings, Thelma C.; Postma, Alex V.; Bezzina, Connie R.; Bouma, Berto J.; et al.
Abstract: Background: Clinical factors are used to estimate late complication risk in adults after atrial switch operation (AtrSO) for transposition of the great arteries (TGA), but heterogeneity in clinical course remains. We studied whether common genetic variants are associated with outcome and add value to a clinical risk score in TGA-AtrSO patients. Methods and results: This multicenter study followed 133 TGA-AtrSO patients (aged 28 [IQR 24–35] years) for 13 (IQR 9–16) years and examined the association of genome-wide single-nucleotide polymorphisms (SNPs) with a composite endpoint of symptomatic ventricular arrhythmia, heart failure hospitalization, ventricular assist device implantation, heart transplantation, or mortality. Thirty-two patients (24%) reached the endpoint. The genome-wide association study yielded one genome-wide significant ( p < 1 × 10 −8 ) locus and 18 suggestive loci (p < 1 × 10 −5 ). A genetic risk score constructed on the basis of independent SNPs with p < 1 × 10 −5 was associated with outcome after correction for the clinical risk score (HR = 1.26/point increase [95%CI 1.17–1.35]). Risk stratification improved with a combined risk score (clinical score + genetic score) compared to the clinical score alone ( p = 2 × 10 −16, C-statistic 0.95 vs 0.85). In 51 patients with a clinical intermediate (5–20%) 5-year risk of events, the combined score reclassified 32 patients to low (<5%) and 5 to high (>20%) risk. Stratified by the combined score, observed 5-year event-free survival was 100%, 79% and 31% for low, intermediate, and high-risk patients, respectively. Conclusions: Common genetic variants may explain some variation in the clinical course in TGA-AtrSO and improve risk stratification over clinical factors alone, especially in patients at intermediate clinical risk. These findings support the hypothesis that including genetic variants in risk assessment may be beneficial. Highlights: A GWAS yielded 1 significant and 18 suggestive loci for event-free survival in adults after the atrial switch operation for TGA. A combined risk score of genetic and clinical risk, improved risk stratification compared to the clinical score alone. This study calls for further research into the impact of genetic variants on outcome in congenital heart disease.